Negative Politeness Strategy in Javanese Dialect In Rimbo Ulu: Pragmatic Analysis - Vera Magria; Anita Mawarni (Jurnal Ilmiah Langue and Parole, 2019)
The purpose of this research is to identify forms of negatives politeness strategy in Javanese Dialect in Rimbo Ulu. This research was conducted by using descriptive qualitative method through applying several stages. The first one was by collecting data through observational method, eliciting technique and advance technique as record and note taking. The data is analyzed by using Yule’s theory and some books that related and supported the theory.for the analyse the data, the researcher used pragmatic identify (referential) method. Next, the data analysis is presented by using informal method.The result of this analysis presented by using informal way. From the ten form calssifies of negative politeness strategy, there are (7) forms are found like: be conventionally, indirect, question (hedge, be pessimistic, minimize the imposition, give deference, apologize, impersonalize